Empowering prospective teachers’ scientific and digital literacy through exploring-resuming integrated criticizing (ERIC) in biology classroom - Ramadani, Shefa Dwijayanti; Lestari, Ayu (Biosfer: Jurnal Pendidikan Biologi, 2024)
Prospective Science teachers need well-developed science and digital literacy to help the process of thinking, learning, communicating, working together, and working with their creativity. Unfortunately, various studies show that students' abilities regarding these two types of literacy still need to improve, especially in first-year students. This study aims to (1) analyze the potential impact of the ERIC learning model with the lesson study-based TPACK framework on science and digital literacy and (2) analyze the contribution of lesson study implementation during ERIC learning to the professional development of educators. This study used a concurrent mixed method. In-depth analysis through lesson study was conducted during the implementation of the ERIC learning model in a quasi-experimental setting. The collected data was then analyzed using the ANCOVA test to reveal the difference in mean scores between the experimental and control classes. At the same time, the results of learning observations and reflection on the lesson study phase were analyzed qualitatively. The results showed that the ERIC learning model with the TPACK framework had a significant effect on scientific and digital literacy. In addition, implementing lesson study enables educators to become more aware of students' learning difficulties and needs and, therefore, develop deeper knowledge about learning requirements